The Procedure of Credit Sales - Irsutami Irsutami; Ayu Novita Sari (Pusat P2M Politeknik Negeri Batam, 2016)
The purpose of the study is to know and understand the preparation, paying, and reporting of Income Tax Article 23 on the use the procedure is a step-by-step phasing and the order of the work in order to achieve objectives efficiently and effectively. In carrying out its operational activities of the company must have a standard operational procedure in order for any activity that occurs in the company running smoothly and more? Writing this final Task is devoted on the discussion of the procedures existing in credit sales companies, from the results of the study showed that the procedure of credit sales process on PT Agung Toyota Sekupang occurred in processing the documents of the credit constraints, i.e. consumers who will purchase the credits still do not know the procedures that exist in the company so that the sales process be delayed. This research suggests that companies should be more stressed to the salesman for more thorough and unequivocal to the consumer in conveying system of procedures that apply to the company, ask again whether consumers already understand over procedures and requirements that are applied by the company.